Possibility theory and PROMETHEE II for decision aid in engineering design process. Issue 13 (2019) - Sylla, A.; Coudert, T.; Vareilles, E.; Geneste, L.; Aldanondo, M.; Ayachi, R.
Abstract: In many design problems, the designer must select the design solution from among several alternative design solutions. In situations where relevant information to evaluate the design solutions are not available, the evaluation is imprecise and uncertain. Therefore, in order to make the right decision, it is necessary to take into account imprecision and uncertainty in the decision process. In this context, this article presents a multi-criteria decision support approach for the complete ranking of alternative design solutions. The proposed approach allows to take into account the imprecision and uncertainty related to the evaluation of the decision criteria. It is based on the possibility theory and PROMETHEE II ranking method. It is validated using an application dealing with the design of a technical bid solution (a couple of technical system and delivery process) during a bidding process.